The Effect of Tax Planning, Investment Decisions, Company Size, and Corporate Social Responsibility on Profit Management in Transportation Subsector Companies Listed on the Indonesia Stock Exchange for the 2019 – 2022 Period - Suhirman Madjid; Widya Ayu Oktaviani (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to examine the influence of tax planning, investment decisions, company size, and corporate social responsibility on earnings management in transportation subsector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research was conducted because one of the reasons was that there were inconsistencies in research results in previous studies. Descriptive research with quantitative methods that focuses on the research object, namely transportation subsector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample selection method used purposive sampling so that 18 companies were obtained during the 4 years of research, resulting in 72 samples. This research uses secondary data from company websites and the Indonesian Stock Exchange website. The results of this research indicate that the variables of company size and corporate social responsibility have a negative effect on earnings management. Meanwhile, tax planning and investment decision variables have no effect on earnings management. This research provides new insight into the influence of tax planning as measured by the tax retention rate (TRR), investment decisions as proxied by the Price Earnings Ratio (PER), company size, and corporate social responsibility on earnings management, which is beneficial for shareholders, investors, and company management in planning strategies and making the right decisions for the company in the future.